2011
DOI: 10.1115/1.4001270
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of Pipes Conveying Fluids—Part II: Applications and Fluidelastic Problems

Abstract: This paper is the second part of the two-part review article presenting an overview of mechanics of pipes conveying fluid and related problems such as the fluid-elastic instability under conditions of turbulence in nuclear power plants. In the first part, different types of modeling, dynamic analysis and stability regimes of pipes conveying fluid restrained by elastic or inelastic barriers were described. The dynamic and stability behaviors of pinned-pinned, clamped-clamped, and cantilevered pipes conveying fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(26 citation statements)
references
References 262 publications
0
26
0
Order By: Relevance
“…The instability phenomenon in a tube bundle where the tube flexibility direction is different from the flow direction is investigated in [9]. The authors found that increasing the flexibility angle results in a decrease in the critical velocity of fluidelastic instability (FEI) (description of FEI see in [11]).…”
Section: Introductionmentioning
confidence: 99%
“…The instability phenomenon in a tube bundle where the tube flexibility direction is different from the flow direction is investigated in [9]. The authors found that increasing the flexibility angle results in a decrease in the critical velocity of fluidelastic instability (FEI) (description of FEI see in [11]).…”
Section: Introductionmentioning
confidence: 99%
“…Paï-doussis [2] summarized the fruits before 1987. In 2010, the achievements during the past 60 years, especially the progresses of nonlinear vibrations and bifurcations, were overviewed by Ibrahim [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…And several excellent overviews also provide a perspective review on this issue. [19][20][21] Although many aspects of this problem have been studied over the past half-century, most of those achievements were limited within the model of single-span pipe conveying fluid. There are also some literatures about the periodical multi-span pipe conveying fluid, [22][23][24] but in the real working environment, the piping systems are always arbitrary multi-span, and the works concerning the random multi-span pipe conveying fluid are quite limited.…”
Section: Introductionmentioning
confidence: 99%